Synthesis and evaluation of galacto-noeurostegine and its 2-deoxy analogue as glycosidase inhibitors1. Issue 29 (7th August 2015) - Salamone, Stéphane; Clement, Lise L.; Viuff, Agnete H.; Andersen, Ole Juul; Jensen, Frank; Jensen, Henrik H.
<x xml:space="preserve">Abstract</x> An epimer of the known glycosidase inhibitor noeurostegine, galacto-noeurostegine, was synthesised in 21 steps from levoglucosan and found to be a potent, competitive and highly selective galactosidase inhibitor of Aspergillus oryzae β-galactosidase.